A Phenomenological Study of Polemic Regulation of Abortion Law on Medical Emergency Indications in Hospital - Asmariah (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
Abortion is a crucial law in health law. But in reality, abortion with some medical reasons is a legal way to be taken in providing solutions to safety problems related to pregnancy. The polemic of overlapping legal rules that apply and occur between the Health Law and the Criminal Code is certainly a condition that must be addressed wisely through some analysis so that it is expected to find the best middle ground in addressing both matters. This study aims to determine the description of the implementation of abortion on indications of medical emergencies in hospitals associated with abortion law regulations namely the Criminal Code and the Health Act. The research design used in this study is qualitative with descriptive phenomenology approach. This study reveals a picture of the implementation of abortion arrangements based on aspects of medical emergencies that are connected between the Health Law and the Criminal Code regulation of abortion crime. The researcher analyzed the data using Colaizzi analysis, which completes the analysis by re-clarifying the participants. The results of the study found that legal issues regarding abortion regulations indicating medical emergencies as long as it refers to the procedure in accordance with Health Law No. 36 of 2009 then the legal issues regarding the Criminal Code on abortion can not be raised to the surface, because medically abortion provocatus medicinalis or abortion on indications of medical emergencies is an abortion that must be performed on pregnant women in emergency conditions that if not performed abortion can threaten the life of the pregnant woman.